2019
DOI: 10.1111/jgh.14889
|View full text |Cite
|
Sign up to set email alerts
|

Non‐alcoholic fatty liver disease is a potential risk factor for liver injury caused by immune checkpoint inhibitor

Abstract: Background and Aim Because of their survival benefits, immune checkpoint inhibitors (ICIs) are widely administered to patients with various advanced‐stage malignancies. During ICI treatment, drug‐induced liver injury (DILI) occasionally occurs. In particular, hepatic immune‐related adverse events (irAEs) are rare but serious and fatal. In patients with hepatic irAEs, immediate steroid treatment is generally recommended; however, the risk factors for ICI‐associated DILI remain unknown. In the present study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…However, quite recently, Sawada et al . reported that the DDW‐J 2004 scale might be useful for diagnosing and determining whether steroid treatment is required in patients with PD‐1 inhibitor‐associated drug‐induced liver injury 19 . Thus, the DDW‐J 2004 may be utilized for diagnosis of irAE hepatitis; however, further investigation is required.…”
Section: Discussionmentioning
confidence: 99%
“…However, quite recently, Sawada et al . reported that the DDW‐J 2004 scale might be useful for diagnosing and determining whether steroid treatment is required in patients with PD‐1 inhibitor‐associated drug‐induced liver injury 19 . Thus, the DDW‐J 2004 may be utilized for diagnosis of irAE hepatitis; however, further investigation is required.…”
Section: Discussionmentioning
confidence: 99%
“…This may be related to the exclusion criteria of the current study. Hepatitis B virus carriers, cholelithiasis, and fatty liver identified as underlying liver diseases may increase the susceptibility to DILI ( Lewis et al, 2007 ; Massart et al, 2017 ; Sawada et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on clinical trials and observational studies, several factors have been shown to influence the risk of ICI-induced liver injury development or to impact liver toxicity pattern such as the type of ICIs, the dose, or the use of a combination therapy. An underlying liver disease such as non-alcoholic fatty liver disease, a preexisting autoimmune profile, or the type of cancer, such as hepatocellular carcinoma, for which the immunotherapy is prescribed is another important factor ( Brown et al, 2017 ; European Association for the Study of the Liver, 2019 ; Sawada et al, 2020 ). Moreover, patients with prior irAEs due to ICIs are considered to be at risk for new irAEs (hepatic or extra-hepatic) even from a different class of ICIs ( Peeraphatdit et al, 2020 ; Regev et al, 2020 ).…”
Section: Immune Checkpoint Inhibitor-induced Liver Toxicitymentioning
confidence: 99%